The relationship between Mycoplasma and Kawasaki disease in pediatric patients: An updated systematic review and meta-analysis - Min Cheng,; Gaihuan Zheng,; Lu Gao,; Bihong Zhang, (Archives of Rheumatology, 2024)
Objectives: This study aimed to clarify the relationship between Mycoplasma pneumoniae (M. pneumoniae) and Kawasaki disease by conducting an updated systemic review and meta-analysis of published studies. Materials and methods: Studies mentioning M. pneumoniae and Kawasaki disease before October 2022 were included in this meta-analysis. The pooled prevalence was calculated, and the log odds ratio in the random effects model was applied to estimate the pooled prevalence of M. pneumoniae infection in pediatric patients with Kawasaki disease. In addition, the clinical parameters, such as hemoglobin and erythrocyte sedimentation rate, were analyzed. Six studies with a total of 1,859 pediatric patients with Kawasaki disease were enrolled. The focused outcome was the pooled prevalence and clinical parameters. Results: The pooled prevalence of M. pneumoniae infection was statistically significant in pediatric patients with Kawasaki disease. In addition, the values of hemoglobin and erythrocyte sedimentation rate were significantly different between M. pneumoniae-infected and non-M. pneumoniae-infected patients with Kawasaki disease. Other clinical parameters were not significantly different between M. pneumoniae-infected and non-M. pneumoniae-infected patients with Kawasaki disease. Conclusion: The results suggest that M. pneumoniae infection is significantly prevalent in pediatric patients with Kawasaki disease. The lower values of hemoglobin and erythrocyte sedimentation rate in M. pneumoniae-infected patients with Kawasaki disease might be needed to investigate further.